2016
DOI: 10.5194/angeo-34-1-2016
|View full text |Cite
|
Sign up to set email alerts
|

Mass-loading, pile-up, and mirror-mode waves at comet 67P/Churyumov-Gerasimenko

Abstract: Abstract. The data from all Rosetta plasma consortium instruments and from the ROSINA COPS instrument are used to study the interaction of the solar wind with the outgassing cometary nucleus of 67P/Churyumov-Gerasimenko. During 6 and 7 June 2015, the interaction was first dominated by an increase in the solar wind dynamic pressure, caused by a higher solar wind ion density. This pressure compressed the draped magnetic field around the comet, and the increase in solar wind electrons enhanced the ionization of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
67
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 50 publications
(57 reference statements)
9
67
0
Order By: Relevance
“…While the ion cyclotron Mirror mode size 49.3 r 1.5 r O + mode has a higher growth rate, in the presence of heavy ions (e.g., alpha particles), the ion cyclotron growth rate will be suppressed significantly in favor of the mirror mode (Price et al, 1986). It is worth noting that similar scale size ratios have been reported for mirror mode structures formed by water group pickup ions upstream of comets (Schmid et al, 2014;Volwerk et al, 2016). It is yet to be determined whether these holes have been carried by the solar wind from smaller heliocentric distances or if they have been formed farther upstream of Mars as a result of temperature anisotropy introduced by pickup ions and then carried to the point of observation by the solar wind.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…While the ion cyclotron Mirror mode size 49.3 r 1.5 r O + mode has a higher growth rate, in the presence of heavy ions (e.g., alpha particles), the ion cyclotron growth rate will be suppressed significantly in favor of the mirror mode (Price et al, 1986). It is worth noting that similar scale size ratios have been reported for mirror mode structures formed by water group pickup ions upstream of comets (Schmid et al, 2014;Volwerk et al, 2016). It is yet to be determined whether these holes have been carried by the solar wind from smaller heliocentric distances or if they have been formed farther upstream of Mars as a result of temperature anisotropy introduced by pickup ions and then carried to the point of observation by the solar wind.…”
Section: Discussionsupporting
confidence: 53%
“…Mirror mode waves grow in high (the ratio of the plasma thermal pressure to the magnetic pressure) plasma with temperature anisotropy T ⟂ ∕T || > 1, where ⟂ and || denote directions perpendicular and parallel to the background magnetic field, respectively. As such, pickup ions are considered the main source of mirror mode wave generation in the heliosheath and in cometary environments (Burlaga et al, 2007;Glassmeier et al, 1993;Liu et al, 2007;Russell et al, 1987;Volwerk et al, 2016). Mirror mode instabilities have been frequently observed in terrestrial and planetary magnetosheaths where shock compression and field line draping cause perpendicular ion heating that provides favorable conditions for mirror mode instabilities to develop (Califano et al, 2008;Erdös & Balogh, 1996;Hubert & Harvey, 2000;Joy et al, 2006;Lucek et al, 2001;Soucek et al, 2008;Tsurutani et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 67P was found to have a plasma environment that is full of small‐scale density and magnetic field variations and where instabilities and waves are common [ Richter et al , ], complicating the interaction with the solar wind. Volwerk et al [] reported on observations of mirror‐mode waves that were generated following a compression of the plasma environment due to increased solar wind dynamic pressure. A population of suprathermal electrons (∼10–100 eV) has been observed continuously after arrival, although with significant variations in both energy and flux over time [ Clark et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…The 40 origin and physical mechanism behind the various 41 components of the observed electron distributions is 42 unclear, but must be understood to disentangle the 43 cometary plasma dynamics. 44 …”
mentioning
confidence: 99%